2016
DOI: 10.15575/jpi.v28i2.543
|View full text |Cite
|
Sign up to set email alerts
|

MANAJEMEN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM (Studi Kasus di Institut Pertanian Bogor)

Abstract: ABSTRAKPenelitian ini bertujuan menggambarkan pelaksanaan pengelolaan/manajemen Pendidikan Agama Islam (PAI) di Perguruan Tinggi Umum (PTU-Non Keagamaan). Lokasi yang dipilih adalah Institut Pertanian Bogor (IPB). Penelitian ini menggunakan teknik studi kasus, karena itu termasuk penelitian kualitatif. Data diperoleh dengan cara melakukan wawancara mendalam, analisis dokumentasi dan pengamatan partisipatif. Hasil penelitian menunjukkan bahwa pelaksanaan manajemen PAI di IPB secara umum meliputi: 1) Program pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This phenomenon also shows that radicalism is not only in the form of anarchism but also in Islamic thought itself. This can be seen in the field of fiqh of worship to the application of Islamic law in everyday life [4]. This condition will certainly affect a person's thinking style within the framework of a tolerant, inclusive and moderate religious life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon also shows that radicalism is not only in the form of anarchism but also in Islamic thought itself. This can be seen in the field of fiqh of worship to the application of Islamic law in everyday life [4]. This condition will certainly affect a person's thinking style within the framework of a tolerant, inclusive and moderate religious life.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of all elements in efforts to prevent radicalism is very much needed [2], [3]. In this context, to eliminate the formation of exclusive religious groups, everyone needs to be mature in understanding the diversity that exists in Indonesia, especially to help the existence of the state [4]. The Indonesian diaspora abroad is one of the vulnerable parties to be infiltrated by extreme thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…However, several previous studies revealed that there was boredom among students in studying IRE due to the lack of learning innovations carried out at HE [2,8,9]. In addition, another finding is that the teaching style of lecturer also determines IRE learning motivation, so that it is closely correlated with high or low learning achievement [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Sundary (2010) mengemukakan bahwa setiap individu harus memperhatikan bagaimana etika, kewajiban, dan hak serta jaminan dalam bekerja yang merupakan salah satu bentuk idealisme dalam internalisiasi prinsip-prinsip dalam bekerja. Senada dengan itu, Hidayatullah (2013) Pada tabel 3 dapat dilihat bahwa work engagement yang dimiliki responden berada pada kategori rendah sebanyak 1 orang (1,5%), sedang 52 orang (76,5%), dan tinggi 15 orang (22,1%). Pada dukungan sosial, responden berada pada kategori rendah sebanyak 3 orang (4,4%) dan sedang 65 % (95,6).…”
unclassified